Uncertainty associated with the indication of verified weighing instruments - Becerra Santiago, Luis Omar (2021)
In the present work the uncertainty associated to the indication in use of verified non-automatic weighing instruments is estimated according to the international recommendation OIML R76. This recommendation of the International Organization of Legal Metrology (OIML) serves as the basis for the verification for most of countries, however, the uncertainty associated to results of verified instruments during its use are not know explicitly.